Moral and Moorean Incoherencies - Andres Soria Ruiz; Nils Franzén (Ergo, An Open Access Journal of Philosophy)
It has been argued that moral assertions involve the possession, on the part of the speaker, of appropriate non-cognitive attitudes. Thus, uttering ‘murder is wrong’ invites an inference that the speaker disapproves of murder. In this paper, we present the result of 4 empirical studies concerning this phenomenon. We assess the acceptability of constructions in which that inference is explicitly canceled, such as ‘murder is wrong but I don’t disapprove of it’; and we compare them to similar constructions involving ‘think’ instead of ‘disapprove’—that is, Moore paradoxes (‘murder is wrong but I don’t think that it is wrong’). Our results indicate that the former type of constructions are largely infelicitous, although not as infelicitous as their Moorean counterparts.